Nonlinear associations between environmental factors and lipid levels in middle-aged and elderly population in China: A national cross-sectional study - Li, Hao; Ge, Miao; Pei, Zehua; He, Jinwei; Wang, Congxia (The Science of the total environment, 2022)
Blood lipid is an important factor affecting cardiovascular disease in middle-aged and elderly people. At present, the associations between environmental factors and blood lipid level in elderly people has been controversial, and the nonlinear effect of their relationship is lack of research. This study used data from a national cross-sectional survey of blood lipid levels in 13,354 subjects and data from environmental monitoring sites. Logistic regression was used to measure the relationship between the basic characteristics of the study population and blood lipid levels. After controlling the confounding factors, the nonlinear associations between environmental factors and blood lipid levels of middle-aged and elderly people in different geographical regions were studied by random forest model. The risk of dyslipidemia is significantly higher in middle-aged women, obese people, elderly people, and urban people. Smoking and alcohol consumption increase the risk. The associations between environmental factors and lipid levels of middle-aged and elderly people are nonlinear, the correlation effect between air pollutants and blood lipid level is mainly shown in northern China, and the correlation between meteorological factors and blood lipid level is more obvious in southern China. This study shows that the associations between environmental factors and lipid levels in middle-aged and elderly population are nonlinear and have regional differences. Therefore it should be considered in optimizing the allocation of public health resources and preventing and controlling environmental exposure of middle-aged and elderly population. [Display omitted] •The risk of dyslipidemia is higher in women, obese people, elderly people, and urban people.•Smoking and alcohol consumption increase the risk.•The associations between environmental factors and lipid levels of middle-aged and elderly people are nonlinear.•The correlation effect between air pollutants and blood lipid level is mainly shown in northern China.•The correlation between meteorological factors and blood lipid level is more obvious in southern China.